Determinants of cancer incidence and mortality among people with vitamin D deficiency: an epidemiology study using a real-world population database - Lai, Yi-Chen; Chen, Yu-Han; Liang, Fu-Wen; Wu, Yu-Cih; Wang, Jhi-Joung; Lim, Sher-Wei; Ho, Chung-Han (Frontiers in Nutrition, 2023)
This study aimed to investigate the determinants of cancer incidence and mortality in patients with vitamin-D deficiency using a real-world population database. We utilized the International Diagnostic Classification Code (ICD9:268 / ICD10: E55) to define patients with vitamin-D deficiency. Additionally, Cox regression model was used to estimate overall mortality and identify potential factors of mortality in cancer patients. In 5242 patients with Vitamin-D deficiency, the development of new-onset cancer was 229 (4.37%) patients. Colon cancer was the most prevalent cancer type. After considering confounding factors, patients who aged at 50-65 and more than 65, respectively, indicated 3.10-folds (95% C.I.: 2.12-4.51) and 4.55-folds (95% C.I.: 3.03-6.82) cancer This is a provisional file, not the final typeset article incidence compared with those aged<50. Moreover, patients with comorbidities of DM (HR: 1.56; 95% C.I.: 1.01-2.41) and liver disease (HR: 1.62; 95% C.I.: 1.03-2.54) presented the higher cancer incidence rate than those without DM/liver. In addition, Vitamin-D deficiency patients with cancer and dementia history indicated the significant higher mortality risk (HR: 4.04; 95% C.I.: 1.05-15.56) than those without dementia. In conclusion, our study revealed that vitamin-D deficiency patients with liver disease had an increased incidence of cancer, while those with dementia had an increased mortality rate among cancer patients.